“It’s like ‘liquid handcuffs”: The effects of take-home dosing policies on Methadone Maintenance Treatment (MMT) patients’ lives - Frank, David; Mateu-Gelabert, Pedro; Perlman, David C.; Walters, Suzan M.; Curran, Laura; Guarino, Honoria (Harm reduction journal, 2021)
Methadone Maintenance Treatment (MMT) is widely recognized as one of the most effective ways of reducing risk of overdose, arrest, and transmission of blood-borne viruses like HIV and HCV among people that use opioids. Yet, MMT's use of restrictive take-home dose policies that force most patients to attend their clinic on a daily, or near-daily, basis may be unpopular with many patients and lead to low rates of treatment uptake and retention. In response, this article examines how clinics' take-home dosing policies have affected patients' experiences of treatment and lives in general. This article is based on semi-structured, qualitative interviews with a variety of stakeholders in MMT. Interviews explored: reasons for engaging with, or not engaging with MMT; how MMT is conceptualized by patients and treatment providers (e.g., as harm reduction or route to abstinence and/or recovery); experiences with MMT; perception of barriers to MMT (e.g., organizational/regulatory, social) and how MMT might be improved to support peoples' substance use treatment needs and goals. Nearly all of the patients with past or present MMT use were highly critical of the limited access to take-home doses and consequent need for daily or near daily clinic attendance. Participants described how the use of restrictive take-home dose policies negatively impacted their ability to meet day-to-day responsibilities and also cited the need for daily attendance as a reason for quitting or avoiding OAT. Responses also demonstrate how such policies contribute to an environment of cruelty and stigma within many clinics that exposes this already-stigmatized population to additional trauma. Take-home dose policies in MMT are not working for a substantial number of patients and are reasonably seen by participants as degrading and dehumanizing. Revision of MMT regulations and policies regarding take home doses are essential to improve patient satisfaction and the quality and effectiveness of MMT as a key evidence-based treatment and harm reduction strategy.